Rabbit Antithymocyte Globulin Causes Blastomyces and Histoplasma Antigenemia. (28th March 2019) - Kaur, Amrit; Eberlein, Michael; Klesney-Tait, Julia; Durkin, Michelle M; Wheat, L Joseph; Gajurel, Kiran
Abstract: Rabbit antithymocyte globulin (rATG) is known to yield false-positive Histoplasma antigenemia. The fourth generation MiraVista Histoplasma antigen assay was modified to block this effect (MiraVista Diagnostics, Indianapolis, Indiana). We report a case of rATG-induced false-positive Blastomyces and Histoplasma antigenemia in a lung transplant recipient despite modifications of these antigen assays.